Effective and efficiency of account receivable: case study at CTRM Aero Composites Sdn Bhd / Zuraida Md Yatim - Md Yatim, Zuraida (2009)
Account Receivable is amounts that customers owe from the company for product that have been sold as well as amounts that may be due from suppliers such as for returns of merchandise. A company uses this account to record the amounts it is owed by its customers. In other words, sales made on credit are reflected in accounts receivable. The issues in this study are about the credit and collection policies and procedures practice in the company and how the credit policy helping in reducing the days of collecting receivables? From the issue, researcher wants to identify the effectiveness and efficiency of account receivable management in the company and make comparison between the actual theories of amount receivable with the practice of the company. The data of this study are gathered from both primary and secondary data. Ratio analysis has been used to compare the company performance for five years. It has been identified in the findings that the company has adapted the actual theories of account receivable in their operation. However, a further study needs to be carried on because the difference company using the difference accounts receivable practice. Base on the result of this study, some recommendation has been proposed which hopefully can help them to improve their business performance in the future.